2023
DOI: 10.37251/jber.v4i2.313
|View full text |Cite
|
Sign up to set email alerts
|

Association of Learners Academic Performance with the Preparedness and Competence in the Implementation of Modular Learning Among Secondary School Teachers at Lanao del Norte

Janisa I. Pangandaman,
Hamdoni Pangandaman

Abstract: Purpose of the study: Part of the challenge in the paradigm shift of the Philippine education system during the pandemic is the adoption and implementation of modular learning in pursuit of the continuity of learning and the promotion of learners' academic performance. This study inquired about the secondary school teachers' preparedness and competence in implementing modular learning and its relationship to learners' academic performance. Methodology: Descriptive correlational approach with triangulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The range age of 5-6 years old are mostly from Junior Kinder or K1. This is in accordance with the study of Pangandaman (1996) which showed that the pupils enrolled at Grade One is at the age of seven years old which is suited after the K2 when they proceed to Grade One. Moreover, Pangandaman said that this is an age which is generally considered by psychologists as the right age to start schooling since they have reached already the age of reasoning and the maturation period.…”
Section: Descriptive Profile Of the Preschool Pupils 431 Agesupporting
confidence: 92%
See 1 more Smart Citation
“…The range age of 5-6 years old are mostly from Junior Kinder or K1. This is in accordance with the study of Pangandaman (1996) which showed that the pupils enrolled at Grade One is at the age of seven years old which is suited after the K2 when they proceed to Grade One. Moreover, Pangandaman said that this is an age which is generally considered by psychologists as the right age to start schooling since they have reached already the age of reasoning and the maturation period.…”
Section: Descriptive Profile Of the Preschool Pupils 431 Agesupporting
confidence: 92%
“…On the aspect of classroom management, Pangandaman (1996) recommended in his study that, in maintaining discipline in the classroom, the teacher should assert her authority as the head of the classroom. She added that "problems should be given immediate attention if we are to improve school education in the Islamic City of the South".…”
Section: Related Studiesmentioning
confidence: 99%